2010
DOI: 10.1172/jci36125
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic downregulation of human disabled homolog 2 switches TGF-β from a tumor suppressor to a tumor promoter

Abstract: The cytokine TGF-β acts as a tumor suppressor in normal epithelial cells and during the early stages of tumorigenesis. During malignant progression, cancer cells can switch their response to TGF-β and use this cytokine as a potent oncogenic factor; however, the mechanistic basis for this is poorly understood. Here we demonstrate that downregulation of disabled homolog 2 (DAB2) gene expression via promoter methylation frequently occurs in human squamous cell carcinomas (SCCs) and acts as an independent predicto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
103
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(106 citation statements)
references
References 59 publications
3
103
0
Order By: Relevance
“…Dab2 may be a tumor suppressor, but in late cancer stages it is also functionally important for tumorigenesis by promotion of EMTmediated metastasis (Prunier and Howe, 2005;Chaudhury et al, 2010). During the progression of human squamous cell carcinoma, downregulation of Dab2 switches transforming growth factor-b from tumorsuppressor to tumor-promoting functions (Hannigan et al, 2010). Clearly, Dab2 appears to have a dual role in tumor progression.…”
Section: Discussionmentioning
confidence: 99%
“…Dab2 may be a tumor suppressor, but in late cancer stages it is also functionally important for tumorigenesis by promotion of EMTmediated metastasis (Prunier and Howe, 2005;Chaudhury et al, 2010). During the progression of human squamous cell carcinoma, downregulation of Dab2 switches transforming growth factor-b from tumorsuppressor to tumor-promoting functions (Hannigan et al, 2010). Clearly, Dab2 appears to have a dual role in tumor progression.…”
Section: Discussionmentioning
confidence: 99%
“…In carcinomas, many tumors lose the growth inhibitory response to TGF-b, but still respond to this ligand but in a protumorigenic manner, such as increased migration, invasion, and epithelial-mesenchymal transition (EMT). Thus, depending on the tumor type and the stage of tumor progression, TGF-b may potently suppress or promote cancer progression through direct actions on the tumor cells (Gomis et al 2006b;Hannigan et al 2010), presumably through its control over differential gene expression programs (see below).…”
Section: Inhibition Of Cell Proliferationmentioning
confidence: 99%
“…Taking into account the many activities of TGF-b and its pleiotropic actions, major efforts focus on identifying alternative targets that influence the TGF-b signaling pathway, with a strong incentive to identify drugs that might block TGF-b's tumor progressing activities while sparing tumor-suppressing activities. Many studies identified pivotal intratumoral players that regulate such a balance-for example, disabled homolog 2 (DAB2), which is epigenetically down-regulated in human SCCs, resulting in attenuation of TGF-b tumor suppressor activity to enable TGF-b tumor-promoting activities, including promotion of cell motility, anchorage-independent growth, and in vivo tumor growth (Hannigan et al 2010). Another example includes the pivotal role played by differential expression of three isoforms of C/EBPb that are generated by usage of distinct translational start sites during tumor progression.…”
Section: Future Directions With Tgf-b Blockadementioning
confidence: 99%
“…115,116 Furthermore, Dab2 participates in the endocytosis of TβRII and promotes signaling of TGFβ through canonical Smad signaling. Dab2 can decrease E-cadherin levels and upregulate the mesenchymal marker vimentin 117 demonstrating not only a role for Dab2 in EMT, but also in the regulation of E-cadherin.…”
Section: Lsd1 H3k4mentioning
confidence: 99%